The Influence of Process Oriented Guided Inquiry Learnng (POGIL) and Direct Instruction (DI) Learning Models on Biology Learning Outcomes at MA Daarul Uluum Lido - Tul Azhari, Siti Suraehah; Arief, Zainal Abidin; Wibowo, Sigit (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
The decline in learning outcomes and student interest is a serious concern in the learning process. The selection of inappropriate learning methods can affect the learning process and outcomes. The Pogil model is one of the alternatives to increase students' interest and learning outcomes. This study aims to explore the effectiveness and advantages of Pogil compared to direct instruction in biology subjects. This research is an experimental research. The results of the study showed that there were student learning outcomes with the pogil model that were superior compared to the direct instruction model in biology subjects with the results of Fcal = 11.4 > Ftabel = 3.96 at a significance level of 0.05. The results of the study showed the influence of interaction between the learning model (pogil and direct instruction) and interest on learning outcomes from the results of Fcal = 4.40 > Ftabel = 3.96 at a significance level of 0.05. The results of the study also revealed that the learning outcomes of students, both those who had low interest and high interest in the pogil model, had superior learning outcomes compared to the direct instruction model. The use of the pogil model significantly improved students' learning outcomes and interest in learning compared to the Direct Instruction model. Thus, pogil becomes an effective learning model in overcoming low learning outcomes and students' interest in biology subjects